Determination of arsenic in acid mine drainage and river water in Ranau, Sabah - Sri Shalini Devi Veeraya (2008)
The colorimetric analysis of arsenic (As) in aqueous solution according to the molybdenum blue method was investigated. Maximum absorbance reading can be obtained at λ =880 nm at least 20 minutes after addition of molybdate reagent to the arsenate, As(V) solution. The absorbance-concentration relationship obeyed the Beer- Lambert law at low arsenate concentrations (≤5 µgmL⁻¹) but showed a negative deviation at high (>5 µgmL⁻¹) concentrations. At fixed arsenate concentration, the presence of phosphate ion gave a higher absorbance reading, which increased with the increase in phosphate concentration. Analysis of river water and acid mine drainage( AMD) samples gave total As concentration in the range of 0.013-0.019 µgmL⁻¹ (Mean=0.016f0.003 µgmL⁻¹) and 0.012-0.024 µgmL⁻¹ (Mean=0.017±0.005 µgmL⁻¹), respectively. These values are higher than the WHO guideline value (0.01 µgmL⁻¹) for arsenic concentration in water. Arsenite, As(III), and arsenate, As(V), is dominant in river water and AMD, respectively.